The first external domain of the nonobese diabetic mouse class II I-A beta chain is unique. - Acha-Orbea, H (1987)
The nonobese diabetic mouse is recognized as an important animal model for human insulin-dependent diabetes mellitus. One of the components of susceptibility to this disease has been mapped to the major histocompatibility complex. In this study, full-length cDNA clones encoding the I-A alpha and beta chains from the nonobese diabetic mouse have been isolated and sequenced. They are identical to the sequences previously determined from the H-2d haplotype except for the sequence encoding the first external domain, the leader peptide, and the 5' untranslated region of the I-A beta chain molecule. Most strikingly, there are five consecutive nucleotide substitutions which lead to two radical amino acid changes in a region that is conserved between human and mouse. We suggest that the unique structure of the first external I-A beta chain domain is a major determinant in the disease susceptibility that maps to the major histocompatibility complex of the nonobese diabetic mouse.